Addition of metformin for non-small cell lung cancer patients receiving antineoplastic agents - Wang, Yan; Hu, Yuanyuan; Wang, Ting; Che, Guowei; Li, Lu (Frontiers in Pharmacology, 2023)
Background and purpose Previous studies have found that metformin can inhibit tumor growth and improve the outcome of cancer patients. However, the association between the addition of metformin and survival in non-small cell lung cancer (NSCLC) patients receiving antineoplastic agents such as chemotherapy drugs, epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and immune checkpoint inhibitors (ICIs) remains unclear. This study aimed to evaluate the effect of metformin in NSCLC patients who received the above antineoplastic therapies. Methods Several electronic databases were searched up to September 10, 2022, for relevant studies. The primary and secondary outcomes were overall survival (OS) and progression-free survival (PFS), comparing patients with and without the addition of metformin. The hazard ratios (HRs) and 95% confidence intervals (CIs) were combined, and all statistical analyses were performed by using STATA 15.0. Results A total of 19 studies involving 6419 participants were included, and six of them were randomized controlled trials. The overall pooled results indicated that the addition of metformin improved OS (HR=0.84, 95% CI: 0.71-0.98, P=0.029) and PFS (HR=0.85, 95% CI: 0.74-0.99, P=0.039). However, subgroup analysis based on the treatment and comorbidity of diabetes mellitus demonstrated that improvements in OS and PFS were observed only in diabetic and EGFR-TKI-treated patients (OS: HR=0.64, 95% CI: 0.45-0.90, P=0.011; PFS: HR=0.59, 95% CI: 0.34-1.03, P=0.061). Conclusion Overall, this meta-analysis found that metformin use could improve the outcome of diabetic patients receiving EGFR-TKIs. However, no significant association between the addition of metformin and the survival of nondiabetic NSCLC patients receiving chemotherapy or ICI therapy was identified based on the current evidence.